Digitalisasi Media Promosi Desa Wisata Penglipuran Bali Melalui Program Magang Bersertifikat - Rokhani, Rokhani; Hafidhuddin, Muhammad Aziiz (Rumah Jurnal UNEJ, 2022)
The existence of digital technology today that has become a mandatory tool that is easy to use for good or bad with a wide and unlimited reach is social media. Penglipuran Tourism Village as one of the leading tourist villages in Bali is still not maximal in utilizing social media, especially the simplest Instagram. Certified Internship Program managed by Pigijo and Kemendikbudristek is expected to increase the digitization of tourist villages that are partners. Penglipuran became one of the partners assigned to the group of 2 vanguard pigijo tourist village to digitize and produce external in the form of digital content and tour packages. The result of this activity or program is able to produce digital content, share the science of digitalization to the relevant villages, so that the management of social media penglipuran tourism village becomes better and has an impact on the economy of the local community by attracting the attention of social media users to visit Penglipuran.